Influence Of Leadership, Work Culture And Work Facilities On The Performance Of Management Agency Employees Majene District Regional Disaster - Said, Muh; Jalante, Andi; Syam, Indah Tri Saputri (STIE Amkop Makassar, 2025)
This research aims to analyze: 1) The influence of leadership on the performance of employees of the Regional Disaster Management Agency of Majene Regency 2) The influence of work culture on the performance of employees of the Regional Disaster Management Agency of Majene Regency 3) The influence of work facilities on the performance of employees of the Regional Disaster Management Agency of Majene Regency. This research uses quantitative methods. The research was carried out at the Majene Regency Regional Disaster Management Agency office. This research distributed questionnaires to 59 respondents. The method used is a quantitative method by testing hypotheses, namely Validity Test, Reliability Test, Classical Assumption Test, Multiple Regression Analysis, T Test, F Test, and Coefficient of Determination. The results of the research show that leadership has a positive and significant effect on the performance of employees of the Regional Disaster Management Agency of Majene Regency in the second variable work culture has a positive and significant effect on the performance of the Regional Disaster Management Agency of Majene Regency in the third variable work facilities have a positive and significant effect on employees of the Regional Disaster Management Agency Majene Regency In the simultaneous test, namely the variables of leadership, work culture and work facilities, have a positive and significant effect on the performance of employees of the Majene Regency Regional Disaster Management Agency while the Determination test contributed 61.3% to employee performance, while the rest was influenced by other variables not included in the research.